Various Games For Improving The Focus Attention And Its Effect On The Accurate Performance Of Some Volleyball Skills - Naji, Saif Alaa; Noori, Hayder Abdulrazzaq (International Journal of Psychosocial Rehabilitation, 2020)
Games are one of the areas that help in building the student’s personality, by giving him opportunities to express himself, his capabilities and creativity, and it is also a field rich in activities that satisfy students need for movement, meditation, thinking and creativity, which is gained through the exercise of physical, psychological exercise and skills, and the focus of attention is among the important aspects of attention, which has proven its impact on the level of performance in various sporting events, it plays an active role in the accuracy of the performance of some skills and also mobilizes the psychological strength associated with performance is the influencing a Stronger on the accuracy and clarity of the goal and from these volleyball games, and the serve skill is one of the attacking skills and defending the court, both of which are influencing in this game, as the team cannot continue to score points without a Proficiency , therefore the volleyball players must realize that the serve and defense are not just Crossing the ball over the net, but they must perform them accurately and direct the ball in them to a place inside the competing team’s court , through which it is possible to achieve a direct point for the team. Learning is more difficult and more complicated than traditional exercises and these exercises sometimes may strain the student so that you must enter some games that can give a pleasant atmosphere and at the same time achieve the goal of training, these games can become an effective tool in performance, so the importance of research came Whoever is trying to introduce some games that improve the focus of attention that can improve the accuracy of performance in the skills of defending the court and the serve by his ability to contribute consciously and control his movement skill that contributes to the success and superiority of the team as an integrated unit by scoring a point (goal).